Leaching of Ni and Cu from mine wastes (tailings and slags) using acid solutions and A. ferrooxidans - Muñoz, A. [UNESP]; Bevilaqua, D. [UNESP]; Garcia, O. [UNESP] (Trans Tech Publications, 2009)
The objective of this work is to evaluate the acidic and biological leaching of tailings containing Ni/Cu from a flotation and smelting plant. Acidithiobacillus ferrooxidans, strain LR, was used for bioleaching at pH 1.8 and chemical controls were run parallel to that. The acidic leaching was done within 48 hours at pH 0.5 and 1.0. In the slag inoculated flasks the redox potential was high (600 mV), thus indicating oxidative bacterial activity, however, the obtained results after 15 days showed only around 13% Ni and 8% Cu extractions, which were not different to those of the controls. For the flotation tailings bioleaching extractions were approximately 45% for Ni and 16% for Cu while differing figures were obtained for the chemical controls. These were 30% and 12% respectively. Here we could observe that the presence of bacterial activity led to a higher solubility of Ni. Acid leaching of slag showed higher nickel and copper extractions: 56% and 24% respectively at pH 0.5 and 21% and 11% at pH 1.0. However, the acid consumption was 320 and 150 Kg/ton of slag, respectively, both much higher than in bacterial assays. These results indicated that Ni and Cu solubilization from the slag is acid dependent no matter the redox potential or ferric iron concentration of the leaching solution. For flotation tailings, acid treatment showed extractions of 23% for Ni and 16% for copper at pH 0.5 and 22% and 28%, respectively at pH 1.0. The acid consumption was also higher: 220 and 120 Kg/ton, at pH 0.5 and 1.0, respectively. Based on own findings we could observe that acid leaching is found to be more effective for slag, though the acid consumption is much higher, while for the flotation tailings, bacterial leaching seems to be the best alternative. © (2009) Trans Tech Publications.
Keywords: A.ferrooxidans; Bioleaching; Slag; Tailings; Acid consumption; Acid leaching; Acid solutions; Acid treatments; Acidic leaching; Acidithiobacillus ferrooxidans; Bacterial activity; Bacterial leaching; Chemical controls; Copper extraction; Ferric iron; Ferrooxidans; Leaching solution; Mine wastes; Redox potentials; Smelting plant; Acids; Bacteriology; Bottles; Flotation; Metal recovery; Mining; Nickel; pH; Secondary batteries; Slags; Solubility; Copper smelting